The Effect Of Finger Puppet On Pain Intensity During Infusation In Preschool Children - Sukmandari, Ni Made Ari; Pradnyani, Ida Ayu Putu Dewi; Sukriyanti, Putu Ari (Poltekkes Kemenkes Jakarta III, 2024)
The main stressor for children when undergoing treatment is fear of pain. Untreated pain experiences lead to physiological and psychological consequences in children over a long period of time. The purpose of this study was to determine the effect of finger puppets on pain intensity during infusion installation in pre-school children in the cilinaya room of RSD Mangusada. This study used quasi-experimental with non-equivalent with control group design post-test only, the intervention group was given finger puppets during infusion installation and the control group accompanied by parents with a sample number of 15 respondents each. The sampling technique is accidental sampling with inclusion and exclusion criteria. Data collection instruments in the form of finget puppet therapy SOPs and FLACC observation sheets were analyzed univariately and bivariately with independent sample tests. The average pain was 3.20 in the intervention group and 7.67 in the control group and the independent sample test found a p value of 0.000 which means that there is an effect of finger puppet administration on pain intensity during infusion in pre-school children. Finger puppets are effectively applied in the pediatric care room of RSD Mangusada to reduce the intensity of pain during infusion installation.